Innovative approaches to architectural design of youth centers in the era of information society (Международный научный журнал «Инженер», 2026)
The article analyzes the objects of cultural purpose oriented to modern youth environment. The results of the study of transformation of volume-planning structure of modern youth spaces in the context of information society development are presented. The architectural and planning concept that can be used as a basis for the creation of a modern youth center is given.